Pengaruh Kompetensi, Motivasi Kerja, dan Lingkungan Kerja terhadap Kinerja Karyawan pada CV. Faris Collection Tulangan Sidoarjo - Oktavia, Cici Fatmawati; Firdaus, Vera (Innovative Technologica: Methodical Research Journal, 2024)
This study aims to determine the influence of Competence, Work Motivation, and Work Environment on Employee Performance at CV. Faris Collection Reinforcement Sidoarjo.This study used a quantitative approach with an associative nature, with a questionnaire in the form of a statement as an instrument which will then be processed with the SPSS version 22 program.This research has the result that competence and motivation have an influence on employee performance, on the contrary the work environment has no effect on employee performance on CV. Faris Collection Reinforcement Sidoarjo.